2005
DOI: 10.1016/j.rmed.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic non-specific interstitial pneumonia: as an “autoimmune interstitial pneumonia”

Abstract: Recently, we have experienced significant number of patients diagnosed with non-specific interstitial pneumonia (NSIP) by open lung biopsy or video-assisted thoracoscopic surgery. The purpose of this study is to compare clinical and pathological features of idiopathic NSIP and NSIP associated with underlying diseases (mainly autoimmune disorders). Forty-six patients with histologically proven NSIP were retrospectively collected. Twenty-four patients had underlying diseases (12 polymyositis/dermatomyositis, 5 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 30 publications
4
51
0
2
Order By: Relevance
“…NSIP could be considered identical to CVD-NSIP, because the clinical characteristics were quite similar despite the presence of underlying CVD [23]. Consistent with this, our previous study showed that in terms of prognosis and responsiveness to therapy, idiopathic NSIP was similar to CVD-NSIP [24].…”
supporting
confidence: 67%
“…NSIP could be considered identical to CVD-NSIP, because the clinical characteristics were quite similar despite the presence of underlying CVD [23]. Consistent with this, our previous study showed that in terms of prognosis and responsiveness to therapy, idiopathic NSIP was similar to CVD-NSIP [24].…”
supporting
confidence: 67%
“…17,19 Within this group of PM/DM patients, however, is a subgroup with anti-Jo-1 autoantibodies that stand out because of their remarkable association with pulmonary function and chest radiographic abnormalities occurring in up to 90% of cases. 12,[15][16][17]19,21,22 This study represents the largest and most complete study of surgical lung biopsies in this unique patient subset and provides some perspectives on the clinical course of this disease given the inclusion of late stage cases derived from lung transplantation and autopsy programs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The anti-Jo-1 tRNA synthetase syndrome has a higher incidence of ILD, relative to classical PM/DM, approximating 90% in some series, and the presence of anti-Jo-1 antibodies correlates with poor patient prognosis. [11][12][13][14][15][16][17][18][19][20][21][22] In this report, we studied the pulmonary histopathologic changes of a select group of IIM patients with the anti-Jo-1 tRNA synthetase syndrome, generating the first and largest biopsy study focused on this specific group of patients.…”
mentioning
confidence: 99%
“…Symptoms of RA usually precede lung involvement, but they can occur simultaneously, or RA can follow the diagnosis of IP [8,16,17]. The most frequent respiratory symptoms are progressive dyspnoea and dry cough even if, in many cases, dyspnoea on exercise may be masked by inactivity due to polyarthritis.…”
Section: Clinical and Laboratory Featuresmentioning
confidence: 99%